Physical, physiological and perceptual match femands of amateur mixed gender touch players - Vickery, W.; Harkness, A. (Journal of Sports Science & Medicine, 2017)
The purpose of this study was to provide a position specific (middle, link [male], link [female], wing) analysis of mixed gender touch on the physical physiological and perceptual demands of amateur players during match-play across a season. Distance and speed measures were obtained through the use of 10-Hz global positioning system devices, whilst telemetric heart rate devices were used determine a range of physiological measures. Players also provided a rating of perceived exertion following each match. The greatest physical demand was associated with the middle playing position by comparison to all others (Distance travelled =5.00 m·s-1 effect size [ES]: 0.01-0.13; average distance =5.00 m·s-1 ES: 0.11-0.38). Those playing as a middle also displayed a greater physiological (Mean heart rate ES: 0.05-0.13) and perceptual demand (rating of perceived exertion ES: 0.01-0.04). However, most measures reported only a trivial effect between each playing position. The findings provide an insight into the differing demands associated with the different playing positions within mixed gender touch which practitioners can use to provide more position-specific conditioning programs.